1986
DOI: 10.1002/cne.902430109
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis in reptilian cortical structures: 3H‐thymidine autoradiographic analysis

Abstract: Histogenesis was studied in forebrain cortical areas of two reptiles, Emys orbicularis and Lacerta trilineata, by using tritiated thymidine autoradiography. Four areas were considered: the dorsomedial, the general (dorsal), and the lateral cortices, and the dorsal ventricular ridge (DVR). The bulk of neurogenesis in these four pallial fields proceeds within a short period of 8-9 days, between developmental stages 15 and 18 in Emys and stages 32-34 in Lacerta. Lateral-to-medial as well as anterior-to-posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 15 publications
10
78
0
Order By: Relevance
“…Tsai et al (1981a) similarly concluded from their autoradiographic data that most of the cells born on days 6 -7 are neurons and that most of the glia are born after day 10 of embryogenesis (Goffinet et al, 1986). This is consistent with our unpublished observation that the small and irregularly shaped nuclei typically found in glia are more frequently labeled when BrdU is injected after 8 d of incubation.…”
Section: Methodological Concernssupporting
confidence: 85%
See 2 more Smart Citations
“…Tsai et al (1981a) similarly concluded from their autoradiographic data that most of the cells born on days 6 -7 are neurons and that most of the glia are born after day 10 of embryogenesis (Goffinet et al, 1986). This is consistent with our unpublished observation that the small and irregularly shaped nuclei typically found in glia are more frequently labeled when BrdU is injected after 8 d of incubation.…”
Section: Methodological Concernssupporting
confidence: 85%
“…From this perspective, the present data are important because they show that migration past older cells is not unique to mammalian neocortex. To determine whether the ability to migrate past older cells evolved twice independently in birds and mammals or just once, in a common ancestors of reptiles, birds, and mammals, it will be necessary to perform more detailed analyses of neurogenesis in amphibians and reptiles (Goffinet et al, 1986). Similarly, the present data show that a subpallial SVZ is not unique to mammals but, again, they leave open the question as to whether the SVZ evolved twice independently in birds and mammals or just once in a common ancestor of these two taxa.…”
Section: Telencephalic Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the dorsal cortex of sauropsids (birds and reptiles) only contains a fraction of the cell types found in the mammalian isocortex (Reiner, 1991;Reiner, 1993), the two antagonistic functional classes of neurons -GABAergic and glutamatergic -are present, suggesting that they were already present in the common ancestor (Goffinet, 1983;Goffinet et al, 1986;Blanton et al, 1987;Blanton and Kriegstein, 1991a;Blanton and Kriegstein, 1991b;Reiner, 1991). The percentage and distribution of inhibitory GABAergic neurons in avian and reptilian pallial regions resemble those seen in mammals (Veenman and Reiner, 1994;Jarvis et al, 2005).…”
Section: Common Subpallial Origin Of Gabaergic Neurons In the Telencementioning
confidence: 99%
“…Adult turtle cortex contains the same two broad functional categories of neurons as the cortex of mammals: excitatory pyramidal and inhibitory stellate neurons (Connors and Kriegstein, 1986). Glutamatergic neurons migrate radially within the pallium and occupy their position in the cortex according to an 'outside-first to inside-last' neurogenetic gradient (Goffinet, 1983;Goffinet et al, 1986). In turtle dorsal cortex, GABAergic neurons represent only 6% of all neurons (Blanton et al, 1987), compared with a 10-20% representation in rodents and primates (Parnavelas, 2000;Hendry et al, 1987).…”
Section: Introductionmentioning
confidence: 99%